2020
DOI: 10.1007/s12551-020-00764-8
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Reviews: a Q1 ranked journal in biophysics and structural biology

Abstract: This Editorial for Biophysical Reviews (Volume 12, Issue 5) begins with a description of the two feature articles. The first being the latest in the "Meet the Editors Series" describing Rosangela Itri-the Biophysical Reviews Executive Editor responsible for the South American region. The second feature article is by Alexandra Zidovska, the inaugural winner of the 2020 "Michèle Auger Award for Young Scientists' Independent Research." Next highlighted are the Issue contents, which consist of five Commentaries/Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Thus, the normalization process typifies liberal conditions that assume a 10% sampling error and an equal probability of each variable being critical or non-critical (Nulty, 2008, p. 309). On the flip side, the scientific community adopts the percentile or quartile system to rank academic journals (Serenko and Bontis, 2021), with the 75th percentile or Quartile 1 (Q1) rank being much coveted even among the early-career researchers (Hall, 2020). Adopting the higher precision level of the percentile approach, further analyses of the thirteen CSFs revealed that Customer focus , Top-management commitment , and Supplier quality management (the top-25% TQM constructs) accounted for seven (CF1 and CF2, TMC1 to TMC3, SQM1 and SQM2).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the normalization process typifies liberal conditions that assume a 10% sampling error and an equal probability of each variable being critical or non-critical (Nulty, 2008, p. 309). On the flip side, the scientific community adopts the percentile or quartile system to rank academic journals (Serenko and Bontis, 2021), with the 75th percentile or Quartile 1 (Q1) rank being much coveted even among the early-career researchers (Hall, 2020). Adopting the higher precision level of the percentile approach, further analyses of the thirteen CSFs revealed that Customer focus , Top-management commitment , and Supplier quality management (the top-25% TQM constructs) accounted for seven (CF1 and CF2, TMC1 to TMC3, SQM1 and SQM2).…”
Section: Resultsmentioning
confidence: 99%
“…More can be learnt about the journal at its official Springer-Nature website and also from its social media pages on Twitter and YouTube (Hall 2017 ; Hall 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional details about the design of the award along with the particulars of each of the previous years’ competitions (announcement, rules, and judging process) can be found in the following references (Hall 2019 ; Hall 2020a , b , c ; 2021a , b , c Hall 2022a , b ).…”
Section: Precis Of Issue Contentsmentioning
confidence: 99%
“…More can be learnt about the journal at its official Springer Nature website and also from selected descriptive content released on its social media pages on Twitter and YouTube (Hall 2017;Hall 2020d).…”
Section: Discussionmentioning
confidence: 99%
“…Nominations can be made via email in the form described above to any of the following. For those interested in entering (or nominating another) additional details about the judging and selection of winners for the previous years' competitions can be found in the following references: Hall (2020bHall ( , 2020cHall ( , 2020d; Hall (2021bHall ( , 2021c. The 2020 winner's published review article can be found here (Zidovska 2020) with the 2021 winner's published review article set to appear in the upcoming Issue 4.…”
Section: A Well-written Commentarymentioning
confidence: 99%